THE INFLUENCE OF PARTICIPATION AND COMPETENCE ON VILLAGE FUND MANAGEMENT WITH THE ACCOUNTABILITY VARIABLE AS AN INTERVENING VARIABLE FOR HANDLING THE COVID 19 VIRUS IN 2020 (CASE STUDY IN MAGELANG, CENTRAL JAVA PROVINCE, INDONESIA) - Susetyo, Yani; Roy Sumaryono; Abul Hasal Asy’ari; Nanik Kustiningsih (Dinasti International Journal of Digital Business Management, 2022)
With the COVID-19 pandemic which has an impact on the economy of the community, the Government is trying to take action to help the economy of the community affected by the Covid-19 corona pandemic. One of them is by changing the mechanism for allocating village funds during a pandemic. This study aims to determine the effect of participation and competence of village officials on the management of village funds through accountability for the handling of covid 19 in Tanggulrejo village, Tempuran district, Magelang regency. This type of research is quantitative research with survey method. The population and sample of this study were village officials with a total of 63 respondents. Data collection using questionnaires and data processing with SPSS linear regression and path analysis. The results showed that: (1). Participation, village apparatus competence and accountability have a significant and positive effect on the management of village funds for handling COVID-19; (2). Participation has an effect on the management of village funds mediated by accountability with the Sobel test obtaining a t count of 0.357453 which is smaller than the t table at a significance of 0.05 (1.98). (3) There is no mediating the effect of competence on village fund management by accountability, this is shown from the Sobel test with a t count of .357453 which is smaller than the t table at a significance of 0.05 (1.98).